Assessing the probative value of DNA evidence: guidance for judges, lawyers, forensic scientists and expert witnesses - Puch-Solis, Roberto; Roberts, Paul; Pope, Susan; Aitken, Colin (RSS, 2012)
Practical guidance for judges, lawyers, forensic scientists and expert witnesses on the logical analysis of DNA profiles, and their probative value in criminal proceedings. Explains technical aspects of DNA profiling and how this information should be presented and interpreted in criminal trials.